2019
DOI: 10.1177/1069031x19843912
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Consumer Attitude Toward Culturally Mixed Symbolic Products from Foreign Global Brands in an Emerging-Market Setting: The Role of Cultural Respect

Abstract: The extant literature has not examined the conditions that govern integrative and exclusionary reactions to cultural hybrid products with sufficient detail. Within an emerging-market setting, this study explores how culturally mixed symbolic products (CMSPs) from foreign global brands can avoid antagonistic consumer attitudes. Building on social categorization theory, the authors argue that foreign global brands are viewed as belonging to an out-group and may thus encounter difficulties in tapping local cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 84 publications
(151 reference statements)
1
62
0
Order By: Relevance
“…As observed by Alden et al (1999), the use of global or foreign consumer culture positioning strategies is potentially more relevant in product categories in which consumers "exhibit common behaviors across the world." Specifically, the authors found that high-tech consumer durables and technology products (such as cameras and computers) are more frequently positioned as symbols of a global universal culture (GCCP) as compared with food products, which are more frequently positioned using elements of the local culture (LCCP) (Alden et al, 1999;Guo et al, 2019). More recently, Özsomer (2012) argues that consumers prefer local brands in culturally grounded categories (such as food in which the local icon brands have strong quality associations) and global brands are more appealing for culture-free publicly visible products (e.g.…”
Section: Product Category and Country Micro Image Effectsmentioning
confidence: 99%
“…As observed by Alden et al (1999), the use of global or foreign consumer culture positioning strategies is potentially more relevant in product categories in which consumers "exhibit common behaviors across the world." Specifically, the authors found that high-tech consumer durables and technology products (such as cameras and computers) are more frequently positioned as symbols of a global universal culture (GCCP) as compared with food products, which are more frequently positioned using elements of the local culture (LCCP) (Alden et al, 1999;Guo et al, 2019). More recently, Özsomer (2012) argues that consumers prefer local brands in culturally grounded categories (such as food in which the local icon brands have strong quality associations) and global brands are more appealing for culture-free publicly visible products (e.g.…”
Section: Product Category and Country Micro Image Effectsmentioning
confidence: 99%
“…Therefore, PEDI should advance our understanding of SI as a distributive injustice measurement scale. Hao et al (2016) and Guo et al (2019) reported that local culture (in-group) and nonlocal culture (outgroup) influenced customer purchasing habits and buying power. Guo et al (2019) added that local customers characterized foreign brands as outgroups based on perceived (misperceptions) of nonsimilar cultural characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hao et al (2016) and Guo et al (2019) reported that local culture (in-group) and nonlocal culture (outgroup) influenced customer purchasing habits and buying power. Guo et al (2019) added that local customers characterized foreign brands as outgroups based on perceived (misperceptions) of nonsimilar cultural characteristics. This is consistent with consumer-based studies by Yuan et al (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although companies have introduced cultural themes into their brands as global, local or foreign consumer–culture positioning strategies (Alden et al , 1999; Steenkamp, 2019), only a few studies have empirically tapped into this topic (e.g. Guo et al , 2019; Peng and Xie, 2016). For instance, global brands can employ aspects of a local culture (i.e.…”
Section: Advancing the Theoretical Understandingmentioning
confidence: 99%